Attitude control system for directional drilling bottom hole assemblies - Panchal, Neilkunal; Bayliss, Martin T.; Whidborne, James F. (Institution of Engineering and Technology (IET), 2012)
A general approach for the attitude control of directional drilling tools for the oil and gas industry is proposed. The attitude is represented by a unit vector, thus the non-linearities introduced by Euler angle representations are avoided. Three control laws are proposed, and their stability is proven. Their behaviour is tested by numerical simulation. The merits of the laws from an engineering perspective are highlighted, and some details for the implementation of the laws on directional drilling tools are provided.